The Journal of the Faculty of Medicine implements a transition process to publish articles in English (2017)
The Journal of the Faculty of Medicine (Revista de la Facultad de Medicina) started its operation back in 1932, and has undergone interesting changes in the last decade, achieving greater visibility and impact on the national and international sphere. Similarly, it has managed to maintain the periodicity of its publication and to be included in important bibliographic indexes. Currently, biomedical journals published in English often make a greater impact and rank better in scientific databases in Spanish, thus giving prestige to the institutions that support them (1). Given this scenario, the medium-term objective of this journal is to publish papers in English only, which leads to a series of structural changes in editorial management and administrative academic support in order to maintain the current number of published scientific articles with excellent quality and a greater international visibility and, therefore, with a higher citation possibility.Publishing the results from the scientific activity of authors through papers in scientific journals is very important, since this has been the traditional way of doing so. Thus, a Latin American journal published in English is the perfect medium to present patents and other research products of the authors from this region and the best way to make visible the results of their work in the world.